Patient perception and satisfaction are prudent for assessment and improvement of hospital services: a cross sectional study among OPD patients at ESIC Medical College and Hospital, Faridabad, Haryana - Goyal, Pooja; Singh, Neha; Lukhmana, Shveta (International Journal Of Community Medicine And Public Health, 2017)
Background: It is imperative for hospital managers to understand and estimate consumer perspective in order to identify and address the perceived gap (if any). The present study was conceived to assess quality of OPD services and patient satisfaction in a tertiary level hospital and to determine the remedial measures for improvement of health services as suggested by the patients. Methods: A hospital based, cross sectional, descriptive study was conducted, using exit interviews, among new OPD attendees at ESIC Medical College and Hospital, Faridabad from August-September, 2016. Data thus collected was analyzed using SPSS 17.0. Results: Out of 145 study subjects, 88.9% (129) subjects perceived the quality of services rendered at hospital as good and 11.1% (16) perceived the quality as poor. 80.68% (117) subjects were reportedly satisfied and only 19.31% (28) were dissatisfied with the hospital OPD services. No statistically significant association was observed between the overall perceived quality and socio-demographic variables of study subjects like age, sex, literacy status and occupation. Main reasons for dissatisfaction as reported by patients were poor availability of medicine(s) (46.15%), poor behavior of doctors (38.46%), long queue(s) at OPD (26.92%) and poor staff behavior (26.92%). Remedial measures suggested by patients were improvement in the availability of medicine (31%), doctor's behavior (17%) and increase in patient registration counters (17%), which were in line with the reasons for dissatisfaction. Conclusions: It is likely that the very act of involving respondents in evaluating their health services will make providers more sensitive and alert to patient needs.